Monday

September 1, 2014

September 1, 2014

Posted by **Ariel** on Thursday, April 19, 2012 at 12:06pm.

- Math -
**Steve**, Thursday, April 19, 2012 at 12:39pmg(m(f)) = g(3f) = 5(3f)-6 = 15f-6 = 15(2x^2)-6 = 30x^2 - 6

- Math -
**Ariel**, Thursday, April 19, 2012 at 7:58pmTHANKS STEVE, I REALLY APPRECIATE THE HELP!!

**Answer this Question**

**Related Questions**

Algebra - Let f(x) = x^2 – 3x + 8 and g(x) = x – 5 (a) Find the sum (f + g)(x) ...

Algebra - When Let f (x) = x^2 – 3x + 8 and g(x) = x – 5 Find Find the composite...

Math - Domain of Composite function - Find the domain of the composite function ...

math - how would this equation look: y=f(x+3) when y=f(x)= x^2 would it look ...

calculus - Suppose that f(x)= square root of x and g(x)= 3x-4 and you are asked ...

college algebra - Let f(x) = square root (x + 2) and g(x) = x^2 − 2. ...

Math - Domain of Composite - Find the domain of the composite function . Please ...

Domain of composite function - Can you please help me with the following ...

Domain of composite function - Find the domain of the composite function fog. f(...

college algebra - Let f(x) = 1/x − 2 and g(x) = 1/x − 3 . Determine ...